Concomitant use of low‐dose methotrexate and NSAIDs and the risk of serious adverse events among patients with rheumatoid arthritis. Issue 8 (24th May 2018) - Svanström, Henrik; Lund, Marie; Melbye, Mads; Pasternak, Björn
Abstract: Purpose: Case reports and pharmacokinetic studies have suggested that concomitant use of low‐dose methotrexate and nonsteroidal anti‐inflammatory drugs (NSAIDs) may be associated with increased risk of methotrexate toxicity. This study aimed to investigate the risk of serious adverse events associated with concomitant use of low‐dose methotrexate and NSAIDs, compared with use of methotrexate alone, among patients with rheumatoid arthritis. Methods: The study was conducted as a register‐based cohort study in Denmark, 2004 to 2015, including episodes of concomitant use of methotrexate and NSAIDs (n = 21 536) and control episodes of use of methotrexate alone (n = 21 725). The primary outcome was the composite end point any serious adverse event, including liver toxicity, acute renal failure, and cytopenia. Secondary outcomes were the individual outcome components. Analyses were conducted using proportional‐hazards regression, with adjustment using inverse‐probability‐of‐treatment weighting based on propensity scores. Results: During follow‐up, 110 cases of the primary outcome occurred during concomitant use of methotrexate and NSAIDs (unadjusted incidence rate 12.1 per 1000 person‐years) and 129 during control episodes (11.0 per 1000 person‐years). Concomitant use of methotrexate and NSAIDs was associated with a significantly increased risk of any serious adverse event (weighted hazard ratio 1.40; 95% CI, 1.07‐1.82). In secondary analyses, concomitant use of methotrexate and NSAIDs was associated with a significantly increased risk of acute renal failure and cytopenia. Conclusions: Concomitant use of low‐dose methotrexate and NSAIDs was associated with a significantly increased risk of serious adverse events, expanding on the evidence base for current regulatory recommendations that advocate caution when low‐dose methotrexate and NSAID are coprescribed.